Circulating IgG autoanti-IgE antibodies in atopic patients block the binding of IgE to its low affinity receptor (CD23). Issue 6 (December 1995) - Smith, S J; Jones, N S; Shakib, F
Abstract : Aims —To investigate the ability of circulating IgG autoanti-IgE antibodies from atopic rhinitis patients to block the binding of IgE to its low affinity receptor (FcεRII), also termed CD23. Methods —This involved the use of a well validated flow cytometric method to detect inhibition of FITC labelled IgE binding to human B cells expressing CD23 (RPMI 8866 cell line). Results —Taking inhibition values greater than 20% as being significant, 15 out of 20 IgG anti-IgE containing sera inhibited the binding of IgE-FITC to the RPMI 8866 cells. The inhibitory effect was recoverable in the IgG fraction of serum, but was not related to the titre of either IgG1 anti-IgE or IgG4 anti-IgE, thus suggesting that it might be related to epitope specificity. No such inhibition was demonstrable with rheumatoid sera containing autoanti-IgG (that is, rheumatoid factor), but lacking autoanti-IgE. Conclusions —The capacity of anti-IgE to block the binding of IgE to CD23 has important implications, particularly in terms of upregulation of IgE synthesis and the consequent perpetuation of the inflammatory response.